Teknologi Informasi dan Komunikasi dalam Manajemen Pendidikan: Peluang dan Tantangan Di Era Digital - Sugiyantoro, Sugiyantoro; Apriliantoni, Apriliantoni (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
The rapid development of Information and Communication Technology (ICT) has changed the paradigm of education, including in Islamic education management. However, ICT implementation in the digital age not only offers opportunities such as increased accessibility and efficiency, but also faces complex challenges such as the digital divide, low technological literacy and cybersecurity vulnerabilities. Previous studies have not holistically addressed ICT integration in the context of Islamic education, including alignment with Islamic values and strategic solutions to existing challenges. This study aims to analyze the opportunities and challenges of ICT implementation in Islamic education management, examine its impact on learning quality, and provide strategic recommendations for optimizing ICT utilization. This research uses a qualitative method with a library research approach. Data were collected from various sources such as scientific journals, books, and related documents, then analyzed descriptively-analytically to identify patterns, challenges, and solutions in ICT integration. The results show that ICT plays an important role in improving the efficiency of education management, learning innovation, and expanding academic networks. In the context of Islamic education, ICT integration should also be aligned with ethical values and justice. The findings of this study provide practical implications for policy makers, educational institutions and educators. Strategic recommendations include strengthening digital infrastructure, continuous teacher training, data protection policies and “4P” (Infrastructure, People, Policy, Protection) based approach to ensure inclusive and sustainable digital transformation. This research also serves as a basis for the development of an ICT integration model that is relevant to the values of Islamic education.